2021
DOI: 10.1111/ans.16562
|View full text |Cite
|
Sign up to set email alerts
|

The effect of national public health interventions for COVID‐19 on emergency general surgery in Northland, New Zealand

Abstract: Background The New Zealand government instituted escalating public health interventions to prevent the spread of COVID‐19. There was concern this would affect health seeking behaviour leading to delayed presentation and worse outcomes. The aim of this study was to examine the effects of these interventions on rate and severity of acute general surgical admissions in Northland, New Zealand. Methods A retrospective comparative cohort study was performed. Two cohorts were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Another assessment performed at the Department of Radiology of the University of Massachusetts Medical School reported a reduction of uncomplicated diverticulitis ( p = 0.002), while there was no significant difference in the number of complicated diverticulitis cases ( p = 0.09) [ 23 ]. The same reduction of patients with acute diverticulitis was reported in some observational studies of patients admitted at emergency surgery units in Italy [ 21 ], New Zealand [ 38 ], and the UK [ 22 ].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Another assessment performed at the Department of Radiology of the University of Massachusetts Medical School reported a reduction of uncomplicated diverticulitis ( p = 0.002), while there was no significant difference in the number of complicated diverticulitis cases ( p = 0.09) [ 23 ]. The same reduction of patients with acute diverticulitis was reported in some observational studies of patients admitted at emergency surgery units in Italy [ 21 ], New Zealand [ 38 ], and the UK [ 22 ].…”
Section: Resultssupporting
confidence: 73%
“…The initial search produced 135 potentially relevant articles. After 85 articles were screened for relevance of titles and abstracts, 50 full text articles were further assessed for eligibility and 25 were excluded ( Supplementary Table S1 ); thus, 25 trials were included in the review [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Their characteristics are reported in Table 1 , Table 2 , Table 3 and Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…26 studies described a change in case number of appendicitis and/or appendectomies between comparable time periods before and during the COVID-19 pandemic in adults [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ]. Studies were conducted in 15 countries (as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overall 25.581 patients were analysed: 18,107 before the onset of the pandemic and 7474 during the pandemic [ 16 , 18 , 20 , [23] , [24] , [25] , [26] , [27] , 30 , 31 , [34] , [35] , [36] , 41 , [54] , [55] , [56] , [57] , [58] , [59] ]. During the pandemic 26.6% of patients had complicated appendicitis, compared to 22.2% before the onset of the pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation